Trend and strategy of industrialisation in Sarawak in relation to human resource development / Talib Zulpilip - Zulpilip, Talib (1992)
Industrialisation is planned and promoted as an integral part of overall development of Sarawak. The major objectives of the industrialisation programme are: (1) to broaden and strengthen the State economy, (2) to increase the value added of its major resources, and (3) to generate employment. So far the efforts to diversify the economy have produced positive results as evidenced by the increased sectoral contribution of manufacturing to the Gross Domestic Product of Sarawak. However despite the vast natural resources available, policy makers and planners view the small population and a rather late start in human resource development as possible constraints in the overall development effort. Thus, appropriate strategy must be drawn to ensure that the growth and role of industrialisation would not be adversely affected; however in doing so the small population base and late development of human resource in Sarawak must be taken into account.